2012
DOI: 10.5194/isprsarchives-xxxix-b5-261-2012
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Tree Stem Attributes Using Terrestrial Photogrammetry

Abstract: ABSTRACT:The objective of this work was to create a method to measure stem attributes of standing trees on field plots in the forest using terrestrial photogrammetry. The primary attributes of interest are the position and the diameter at breast height (DBH). The developed method creates point clouds from images from three or more calibrated cameras attached to a calibrated rig. SIFT features in multiple images in combination with epipolar line filtering are used to make high quality matching in images with la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Any calibrated rig removes the need for a scale bar, since the known length of the rig baseline establishes the scale of the scene. To satisfy the other requirements, the rig was designed with five cameras in positions such that no three-camera subset was collinear ( [18] and Figure 1). The five-camera design would be tolerant towards occlusions, since matching between any combination of three cameras would be sufficient to produce a point.…”
Section: Rig and Image Protocol Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Any calibrated rig removes the need for a scale bar, since the known length of the rig baseline establishes the scale of the scene. To satisfy the other requirements, the rig was designed with five cameras in positions such that no three-camera subset was collinear ( [18] and Figure 1). The five-camera design would be tolerant towards occlusions, since matching between any combination of three cameras would be sufficient to produce a point.…”
Section: Rig and Image Protocol Designmentioning
confidence: 99%
“…The algorithm for automatic point cloud computation was a development of the algorithm by Forsman et al [18]. Each image was processed using the VLFeat (VisionLab Features Library) implementation of the Scale Invariant Feature Transform (SIFT) algorithm [22].…”
Section: Point Cloud Constructionmentioning
confidence: 99%
“…The result shows, 85% of the measured trees were within 0.5 m of the field-measured tree locations. A multicamera system was developed in [16], which had five calibrated digital cameras installed on a rig. Five images were simultaneously taken from a single viewpoint, and a point cloud was generated.…”
Section: Introductionmentioning
confidence: 99%
“…As for terrestrial cases, a study to map individual trees in urban environment was reported recently [16]. A multi-camera system was presented in [17], which had five calibrated digital cameras installed on a rig. A point cloud was generated based on the five images simultaneously taken from a single viewpoint, and the DBHs of individual trees in the view were estimated with a root mean squared error (RMSE) of 2.08 cm.…”
Section: Introductionmentioning
confidence: 99%